Nitric oxide donor reveals alterations in interstitial oxygen pressures during skeletal muscle contractions in rats with pulmonary hypertension - Schulze, Kiana Marie (Kansas State University, 2020)
Introduction: Pulmonary hypertension (PH) is a devastating disease characterized by pulmonary vascular dysfunction and exercise intolerance, due, in part, to gas exchange impediments and impaired cardiac function. In the rat model of PH, we sought to determine whether there are also peripheral (i.e. muscle) aberrations in O₂ delivery-to-utilization matching and vascular control that might contribute to poor exercise tolerance. Furthermore, we investigated peripheral effects of the potent vasodilator, nitric oxide (NO) in attenuating these anticipated decrements. Methods: Adult male Sprague-Dawley rats were administered a one-time intraperitoneal injection of monocrotaline (MCT; 50 mg/kg) to induce progressive PH. Echocardiography was utilized to monitor disease progression, and at moderate PH preceding right ventricular (RV) failure, experiments were conducted. Phosphorescence quenching protocols determined the partial pressure of O₂ in the interstitial space (PO₂is) in the spinotrapezius muscle at rest and during contractions under control (SNP (-)) and NO-donor (SNP (+)) superfusion conditions. Results: On average, 3-4 weeks post-injection, MCT rats displayed RV hypertrophy (371 ± 46 vs. 251 ± 9 mg), pulmonary congestion, increased right ventricular systolic pressure (48 ± 6 vs. 20 ± 3 mmHg), and arterial hypoxemia (PaO₂: 63.5 ± 3.5 vs. 83.5 ± 3 mmHg) compared to healthy rats (P ≤ 0.05). No differences were observed in SNP (-) PO₂is kinetics or overall muscle oxygenation between healthy and MCT (P > 0.05), although PO₂is was significantly lower in MCT animals during seconds 10-26 of contractions. SNP (+) unveiled a significantly lower PO₂is and overall muscle oxygenation (AUC: 1730 ± 215 vs. 2789 ± 165) throughout contractions in MCT animals versus healthy (P ≤ 0.05). Conclusions: Our findings reveal that, in small muscle mass exercise in MCT rats, muscle oxygenation impairment is significant only during seconds 10-26 after contraction onset and, while NO effectively augments muscle oxygenation, O₂ delivery-to-utilization matching during contractions is attenuated following increased NO bioavailability in MCT rats. These data support that limitations occurring in whole body exercise, particularly near maximal capacity, may be O₂-delivery-dependent and include impaired NO-mediated vasodilation contributing potentially to a diminished exercise-induced hyperemia and thus exercise intolerance
Keywords: Pulmonary hypertension; Oxygen transport; Skeletal muscle; Exercise; Nitric oxide